2007
DOI: 10.1542/peds.2006-1472
|View full text |Cite
|
Sign up to set email alerts
|

No Improvement in Outcome of Nationwide Extremely Low Birth Weight Infant Populations Between 1996–1997 and 1999–2000

Abstract: No significant changes were detected in birth or mortality rate in extremely low birth weight infants born in Finland during the late 1990s, but some neonatal morbidities seemed to increase. Regional differences in mortality were detected in both cohorts. Repeated long-term follow-up studies on geographically defined very preterm infant cohorts are needed for establishing reliable outcome data of current perinatal care. Regional differences warrant thorough audits to assess causalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
115
3
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 35 publications
(40 reference statements)
18
115
3
8
Order By: Relevance
“…[5][6][7][9][10][11][12]14,[17][18][19]36,37 Some studies present survival rates for live births only, ranging from 0% to 53%. 5,7,10,11,14,[16][17][18]20,36,37,47 Other studies include only infants admitted to the NICU, with survival rates ranging from 0% to 66%. 4,9,[11][12][13][14][15]17,18,20,21,23,24,34 Previous Canadian studies that did not include stillbirth noted survival rates in infants admitted to the NICU of 35.2% to 41.7%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][9][10][11][12]14,[17][18][19]36,37 Some studies present survival rates for live births only, ranging from 0% to 53%. 5,7,10,11,14,[16][17][18]20,36,37,47 Other studies include only infants admitted to the NICU, with survival rates ranging from 0% to 66%. 4,9,[11][12][13][14][15]17,18,20,21,23,24,34 Previous Canadian studies that did not include stillbirth noted survival rates in infants admitted to the NICU of 35.2% to 41.7%.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,10,11,14,[16][17][18]20,36,37,47 Other studies include only infants admitted to the NICU, with survival rates ranging from 0% to 66%. 4,9,[11][12][13][14][15]17,18,20,21,23,24,34 Previous Canadian studies that did not include stillbirth noted survival rates in infants admitted to the NICU of 35.2% to 41.7%. 4,15,24 The survival rate was lower in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse resultado condiz com o baixo emprego de surfactante observado nos nascimentos com peso inferior a 1.000g. Alguns países europeus reservam condutas mais pró-ativas aos recém-nascidos de maior viabilidade 2,18,24,25 , porém cabe comentar que, nesses locais, há parâmetros definidos para o emprego de tais condutas e há participação de familiares no processo de definição desses parâ-metros 26,27 .…”
Section: Introductionunclassified
“…infants with BWs <1000 g or gestational age (GA) <28 weeks. Studies have shown that many of these children survive with significant shortand long-term neurodevelopmental sequelae (Hack et al 1996;Wood et al 2003, Mikkola et al 2005, and a significant proportion of them (2-3%) become blind or severely visually impaired (Mikkola et al 2005;Tommiska et al 2007;Jacobson et al 2009). However, there are few long-term studies specifically addressing the ocular and visual problems in children born extremely preterm (Hebbandi et al 1997;Spencer 2006).…”
Section: Introductionmentioning
confidence: 99%